2017
DOI: 10.18632/oncotarget.22248
|View full text |Cite
|
Sign up to set email alerts
|

Novel piplartine-containing ruthenium complexes: synthesis, cell growth inhibition, apoptosis induction and ROS production on HCT116 cells

Abstract: Piplartine (piperlongumine) is a plant-derived molecule that has been receiving intense interest due to its anticancer characteristics that target the oxidative stress. In the present paper, two novel piplartine-containing ruthenium complexes [Ru(piplartine)(dppf)(bipy)](PF6)2 (1) and [Ru(piplartine)(dppb)(bipy)](PF6)2 (2) were synthesized and investigated for their cellular and molecular responses on cancer cell lines. We found that both complexes are more potent than metal-free piplartine in a panel of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 64 publications
3
32
0
Order By: Relevance
“…The previous research indicates that ruthenium(II) complexes have different effects on the induction of apoptosis in SW480 cells, depending on the ligands in their structure, from a very strong impact where 72% cells were in apoptosis, to moderate, with only 31% apoptotic cells [ 27 ]. In terms of the results related to the ability of ruthenium(II) complexes to induce apoptosis of HCT116 cells, there are results from the previous research that confirm that ruthenium(II) complexes increase the early and late apoptosis of HCT116 in a time- and concentration-dependent manners, but less than oxaliplatin, which is consistent with our results [ 26 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The previous research indicates that ruthenium(II) complexes have different effects on the induction of apoptosis in SW480 cells, depending on the ligands in their structure, from a very strong impact where 72% cells were in apoptosis, to moderate, with only 31% apoptotic cells [ 27 ]. In terms of the results related to the ability of ruthenium(II) complexes to induce apoptosis of HCT116 cells, there are results from the previous research that confirm that ruthenium(II) complexes increase the early and late apoptosis of HCT116 in a time- and concentration-dependent manners, but less than oxaliplatin, which is consistent with our results [ 26 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with previous reports that ruthenium(II) polypyridyl complexes at lower concentrations do not affect the release of LDH enzyme from various tumor cells (HeLa, PC3, LanCap, MCF-7, and MD-MBA 231), but when the cells were treated with higher concentrations of ruthenium(II) polypyridyl complexes, the LDH activity in the culture media increased significantly [ 25 ]. However, the percentages of necrotic cells remain generally low after exposure of colorectal tumor cells to piplartine and arene ruthenium(II) complexes [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Costa et al reported the incorporation of piplartine into a Ru‐Fe complex 86 (Figure ). Piplartine is a plant‐derived molecule with anti‐cancer activity and causes oxidative stress within the cancer cell as a mode of action.…”
Section: Rutheniummentioning
confidence: 99%
“…The Ru‐Fe complexes investigated by Chakraborty and colleagues ( 74 – 85 ), Costa et al ( 86 ) and Batista and colleagues ( 87 – 90 ). The IC 50 (µM) values reported are shown below the chemical structures.…”
Section: Rutheniummentioning
confidence: 99%
“…Piplartine (Figure ) is an amide alkaloid component of Piper species that is widely distributed in the tropical and subtropical regions of the world with commercial, economic and medicinal importance (Bezerra et al, ; Bezerra et al, ). Piplartine has shown cytotoxic and antiproliferative activity in several tumor cell lines, including melanoma (Bezerra et al, ; D’Sousa Costa et al, ). The cytotoxic effect of piplartine seems to be related to DNA damage, leading to cell death both by apoptosis and by necrosis, depending on the concentration used (Bezerra et al, ).…”
Section: Introductionmentioning
confidence: 99%